Manajemen Nyeri untuk Congestive Heart Failure - Tri Wahyuni Ismoyowati; Imelda Sri Desisi Teku; Jen Christin Banik; Rineke Anitya Oryza Sativa (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Congestive Heart Failure (CHF) is a health problem that continues to grow in the world. CHF is the inability of the heart to pump blood to meet the tissue's needs for oxygen and nutrients, resulting in various clinical symptoms, namely chest pain. This paper is a literature review from several data bases, namely Pubmed (NCBI, NIH & AHA) Google Scholar, Proques, Elsiver. The search for articles was limited from 2010-2020 using the keywords “CHF pain therapy”, “Congestive Heart Failure management”, “Congestive Heart Failure pain management”, “Congestive Heart Failure”, “Pain Management Congestive Heart Failure”, “Pain Therapy Congestive Heart Failure ”. The search results obtained are 4 domestic journals and 96 international journals. Based on the results of the analysis, it can be concluded that pain management for patients with CHF obtained several non-pharmacological techniques, namely Watch Distraction Technique, Deep Breath Relaxation Technique, Guided Imaginery Technique, Virtual Reality, Meditation Technique, Murottal Technique, Walking Therapy, Streching and use of hot and cold media. However, the researchers concluded that Deep Breath Relaxation Techniques and Watch Distraction Technique were more effective in reducing pain in patients with CHF (p-value 0,000). Further research is needed to see the effectiveness of pain management in CHF patients using appropriate methods. Keywords: congestive heart failure; management; pain ABSTRAK Congestive Heart Failure(CHF) merupakan masalah kesehatan yang terus berkembang di dunia. CHF adalah ketidakmampuan jantung untuk memompa darah dalam memenuhi kebutuhan jaringan akan oksigen dan nutrisi, akibatnya menimbulkan berbagai gejala klinis yaitu nyeri dada. Tulisan ini merupakan tinjauan literatur dari beberapa database yaitu Pubmed (NCBI, NIH & AHA) Google Scholar, Proques, Elsiver. Penelusuran artikel dibatasi dari tahun 2010-2020 dengan menggunakan kata kunci “terapi nyeri CHF”, “manajemen Congestive Heart Failure”, “manajemen nyeri Congestive Heart Failure”, “Congestive Heart Failure”, “Pain Management Congestive Heart Failure”, “Pain Therapy Congestive Heart Failure”. Hasil penelusuran yang diperoleh adalah 4 jurnal dalam negeri dan 96 jurnal international. Berdasarkan hasil analisis dapat disimpulkan bahwa manajemen nyeri untuk pasien dengan CHF didapatkan beberapa teknik non farmakologis yaitu Teknik Distraksi Menonton,Teknik Relaksasi Napas Dalam, Teknik Guided Imaginery, Virtual Reality, Teknik Meditasi, Teknik Murottal, Walking Therapy, Streching dan penggunaan media panas dingin. Namun peneliti menyimpulkan bahwa terapi Teknik Relaksasi Napas Dalam dan Distraksi Menonton lebih efektif untuk menurunkan nyeri pada pasien dengan CHF (p-value 0,000). Diperlukan penelitian lebih lanjut untuk melihat keefektifan manajemen nyeri pada pasien CHF dengan menggunakan metode yang tepat. Kata kunci: congestive heart failure; manajemen; nyeri